From Judicial Permission to Judicial Governance: Polygamy Regulation under Libyan Family Law (1984–2015) - Masuwd, Mowafg; Barkah, Sami; Aladi, Salem; Alrumayh, Safa; Hasan, Laylay; Omar, Zaynab; Ayad, Nahid (Jurnal Suara Hukum, 2026)
This study analyzes the judicial regulation of polygamy in the Libyan family law using socio-legal and maqasid al-shariʿah framework. Focusing on Law No. 10 of 1984 on Marriage and Divorce and its amendments (1991, 1994, and the 2015 deletion of Article 13), the study traces how polygamy shifted from jurisprudential (fiqhi) permissibility to judicial restriction subject to authorization, contestation, and potential refusal. Using qualitative doctrinal analysis supported by socio-legal contextualization, the research examines how the authorization mechanisms have transformed polygamy from a private spousal privilege to a legally conditioned practice subject to state supervision and refusal. The findings show an institutional shift in the role of Libyan courts from verifying formal requirements to evaluating financial capacity, potential harm, and family welfare, especially after the 1994 “serious reasons” standard. The article argues that these restrictions are better understood as a maqasid-oriented understanding of justice and harm prevention rather than as a departure from Shariʿah. By linking statutory law, judicial discretion power, and socio-political context, the study contributes to the continuous debates on Islamic family law reform, the role of courts in Muslim-majority countries, and the normative foundations for regulating marital practices.